Manuscript and Print in the Late Seventeenth Century: The Case of Morgan Library, MS MA 4431, British Library, MS Egerton 2570, and Richard Baxter's An end of doctrinal controversies (1691). (14th August 2018) - Charlton, Tom; Searle, Alison
Abstract: The leading Puritan divine, Richard Baxter (1615–1691), left behind a complex range of manuscripts at his death. Preparatory work for the forthcoming Oxford University Press editions of his autobiography, Reliquiæ Baxterianæ, and of his complete correspondence has uncovered a lacuna in this manuscript collection and its subsequent cataloguing. This has implications for our understanding of Baxter's manuscript legacy, his intellectual interests, and his writing and publishing practices in the final decades of his life. It also provides a glimpse into authorial and press practice in the late seventeenth century, enriching our understanding of book history and the relationship between manuscript and print at that time.